Parametric study of earth-to-air heat exchanger in Malaysian climate - Ibrahim, Md. Najib; Sanusi, Aliyah Nur Zafirah; Ali, Maisarah; Aziz Ahmed, Soran Hama (2013)
The technology, where the ground was used as a heat sink to produce cooler air, has been an area of interest in Malaysia even before National Green Technology Policy was launched in 2009. This simulation study is based on ASHRAE Weather database, local data collected in previous field studies at Universiti Teknologi Malaysia Skudai Campus in Johor and International Islamic University Malaysia Gombak Campus in Selangor. This study investigates the parameters influencing the cooling potential of Earth-to-Air Heat Exchanger (EAHE).